Improving Diagnostic Procedures in Autism for Girls and Women: A Narrative Review - Cook J; Hull L; Mandy W (Neuropsychiatric Disease and Treatment, 2024)
Julia Cook,1,* Laura Hull,2,* Will Mandy3 1Social, Genetic and Developmental Psychiatry Centre, King’s College London, London, UK; 2Bristol Medical School, University of Bristol, Bristol, UK; 3Department of Clinical, Educational and Health Psychology, University College London, London, UK*These authors contributed equally to this workCorrespondence: Will Mandy, Email w.mandy@ucl.ac.ukAbstract: Biases exist in the diagnostic process for autism spectrum disorder (henceforth “autism”), which result in some girls and women being diagnosed later or missed entirely. Current diagnostic tools may not capture the full range of behavioural presentations of autism, leading to under-identification. This review explores why these biases may occur, and how diagnostic procedures could be adapted to better identify autistic girls and women. We recommend that diagnostic assessments are adjusted to capture a broader range of behavioural exemplars of autism; that camouflaging of autistic traits is taken into account; and that care is taken to ensure co-occurring mental health conditions do not overshadow autism diagnosis. We offer recommendations, building on gold-standard diagnostic guidelines, for how diagnostic procedures can be improved for girls and women.Keywords: autism, girls, women, diagnosis